Biodiversity of Host Plants for Laccifer lacca in Gondia District, Maharashtra, India - Sangode, Virendra K; Gahane, Sandipkumar (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
Lac is mainly produced in India, Thailand, and Indonesia, parts of China, Vietnam and Cambodia. In India Bihar and Maharashtra are the major Lac producing state. Present study was carried out to enhance the production of Lac and multiplication of insect diversity in ecological system as if due to anthropogenic activity and increase in farm lands continuously forest cover has been detrioted by cutting down major host plants of lac insect too, destruction its habitat. Our study promotes and encourage lac culture to increase entrepreneur ship of among women and farmers community of rural agro depended area of district with conservation and identification of host plants Laccifer lacca.